1975
DOI: 10.1016/0021-9797(75)90142-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis-precipitation studies of aluminum (III) solutions. I. Titration of acidified aluminum nitrate solutions

Abstract: Acidified aluminum nitrate solutions were fitrated with alkali (NaOH or KOH) over a temperature range of 24°C to 90°C. A homogeneous distribution of added base was achieved by: (i) in situ decomposition of urea (90°C); and (ii) a novel method involving injection through a capillary submerged in the agitated salt solution.The experimental pH curves are characterized by two plateaus (or platforms) separated by a steep jump in pH. These characteristic features were not previously observed in continuous titration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
4

Year Published

1979
1979
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 19 publications
3
48
0
4
Order By: Relevance
“…Solutions of 0.5 M Al(NO3)3 (Merck 1063) were hydrolyzed by injection, using a Gilson pump (rate 0.015 ml/s, of 0.2 M NaOH (Merck 6498) solution in a specially designed reaction vessel (Vermeulen et al, 1975), until a molar OH/A1 ratio of 2.4 was reached (Kloprogge et al, 1992b). The final solutions were aged for 2 h at 50~ to optimize the All3 content.…”
Section: Pillaring Agentsmentioning
confidence: 99%
“…Solutions of 0.5 M Al(NO3)3 (Merck 1063) were hydrolyzed by injection, using a Gilson pump (rate 0.015 ml/s, of 0.2 M NaOH (Merck 6498) solution in a specially designed reaction vessel (Vermeulen et al, 1975), until a molar OH/A1 ratio of 2.4 was reached (Kloprogge et al, 1992b). The final solutions were aged for 2 h at 50~ to optimize the All3 content.…”
Section: Pillaring Agentsmentioning
confidence: 99%
“…The first inflection point determines the neutralization equivalence of the excess H30 + initially present, the second is acid A13+ (see also Vermeulen et al, 1975). These titration characteristics changed only slightly with titration speed.…”
Section: Titration Curves Of Al(noa)3 Solutionsmentioning
confidence: 93%
“…However, Vermeulen et al (1975) found by microelectrophoretic measurement that the A1 hydroxide particles formed during the titration are positively charged up to pH 10, which suggests that the AI 3+ ions may not have been fully titrated at pH 7.4.…”
Section: Titration Curves Of Al(noa)3 Solutionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Pour eertains, cette 6volution passe par une association en plaquettes, sortes d'~16ments pr6gibbsitiques. Les travaux de Vermeulen et al (1975), puis de Stol et al (1976 sont parmi les plus r6cents qui s'inscrivent dans cette ligne, alors que les r6sultats de la r6sonance magn&ique nucl6aire conduisent Bottero (1979) et Bottero et al (1980) ~ s'opposer it cette conception et fi proposer le passage par une phase d'association tubulaire fi partir d'ions hydroxopolym+res dans lesquels un atome A1 occupe une position centrale avec une coordinence IV --All~(OH)2sOa(H20)~ +.…”
Section: Domaine D'existence Des Monomkres Hydroxyl~s De L'aluminium;unclassified